Balanced Shape Design of an Eccentric Gear - Wei Jiangbo (Jixie chuandong)
A balanced shape design of an eccentric gear is presented,by using the leverage balanced design principle,the balance force on gear tooth is achieved by changing gear shape in the software of UG.After eccentric gear design,the original mechanical strength is retained,the force between the teeth is more evenly,the drive is more smoothly.